Photooxidation of 9-anthraldehyde catalyzed by gold nanoparticles: Solution and single nanoparticle studies using fluorescence lifetime imaging - Wee, Tse-Luen (2012)
The photooxidation of 9-anthraldehyde can be catalyzed by colloidal Au nanoparticles (AuNP) or diamond-supported Au nanoparticles (AuNCD) by using LED excitation at 530 nm. Visible irradiation of the plasmon band of AuNP in an acetonitrile solution of 9-anthraldehyde saturated with oxygen or air results in formation of oxidation products, particularly anthraquinone. The reaction does not occur in the dark or without AuNP. It is also inhibited in nitrogen-saturated solution. An enhanced oxidation activity has been observed with AuNCD. We also examined the catalysis by colloidal or supported Au nanoparticles with millisecond real-time resolution using FLIM and TIRFM techniques to observe the time-resolved events leading to the single nanoparticle, single molecule conversion of 9-anthraldehyde into its endoperoxide, eventually to yield anthraquinone. © 2012 American Chemical Society.